AI Tools in the Development of Supporting Sentences: Insights from Paragraph Writing Classes in an EFL Context - Trong Toan Phan; Vu Diem Thuy Tran (Universitas Pendidikan Ganesha, 2025)
This study aims to investigate first-year English-majored students' perceptions of Grok 3 as a tool for writing supporting sentences at Ho Chi Minh City University of Foreign Languages – Information Technology (HUFLIT), while also exploring the benefits and challenges students may encounter. Through a mixed-methods design, both quantitative and qualitative insights are provided. This study consists of 63 participants, divided into control and experimental groups. Data were gathered from pre- and post-tests, questionnaires, and semi-structured interviews. The results show that students generally found Grok 3 useful, easy to use, and effective in generating ideas, improving paragraph clarity, and supporting future writing tasks. Conversely, some concerns included reduced creativity, lower motivation, the need for detailed prompts, topic misalignment, and ethical or privacy issues. The findings of this study have several important implications for EFL writing instruction, educational technology integration, and AI-assisted learning design.